Lovemarks and beyond: Examining the link between lovemarks and brand loyalty through customer advocacy in the automobile industry - Nayab Javed; Syed Haider Khalil; Amir Ishaque; Syed Majid Khalil (PLoS ONE, 2023)
Purpose Despite the potential for businesses, our understanding of lovemark brands and their consequences is limited. Numerous psychological and brand-related consequences are linked to lovemarks, but the role of influential underlining mechanisms is not fully understood. Inspired by the norms of reciprocity theory, the current study investigates the underlining role of customer advocacy in the relationship between perceived lovemarks and brand loyalty of customers in the automobile industry. Methodology By adopting the survey method, a sample of 478 was drawn from Pakistani automobile customers. Structural equation modelling was used for the analysis. We conceptualised lovemarks and brand loyalty as reflective higher-order constructs that we analysed through a two-stage disjoint analysis. Findings Our results support the conceptualization of lovemarks and brand loyalty as higher-order constructs. The influence of lovemarks and customer advocacy on brand loyalty was statistically significant when we controlled for age, gender, and income. Our findings also reveal that customer advocacy, seen as a company’s positive interactions, mediates and play a key role in influencing the relationship between lovemarks and brand loyalty. Originality This is among the first studies to examine the role of customer advocacy in the lovemarks-brand loyalty relationship. We examined these relationships in the automobile sector of Pakistan, which offers several theoretical and managerial implications for academia and practitioners. The implications are proposed and outlined in this study.